Cryptocurrency and its taxation - Drobotovs, Mihails (Riga Graduate School of Law, 2022)
Since 2008, the emergence of the cryptocurrency market has had a considerable influence on the financial sector and the economy as a whole, including the rise of blockchain technology and the production and presence of new types and numbers of cryptocurrencies. Many researchers recognize the significance and benefits of the cryptocurrency market for the global economic system; however, global economies are less welcoming because blockchain technology allows cryptocurrency to remain unregulated by regulators due to its high anonymity and decentralization, potentially leading to increased opportunities for illegal money circulation. Regulators across the world are discussing whether and how to regulate cryptocurrencies. As a result, it is necessary to go more into this topic, evaluating current taxes and security rules in order to identify potential legislative difficulties and prescribe a plan of action. Currently, the legal framework is insufficient to solve all of bitcoin's challenges, and it does not control all aspects of cryptocurrency transactions and activities. The present legislative framework is unable to deal with the anonymity and decentralization of cryptocurrencies, resulting in their revelation.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Cryptocurrency; Taxation